If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = -9 Reorder the terms: -3 + 8x = -9 Solving -3 + 8x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8x = -9 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = -9 + 3 8x = -9 + 3 Combine like terms: -9 + 3 = -6 8x = -6 Divide each side by '8'. x = -0.75 Simplifying x = -0.75
| .4x+.06(30)=9.8 | | 5x+6=3(x-8) | | 2*x+1=22 | | x(6x-3)+2=6x(x-2)+x | | X+5y=76 | | -5(3c+6)=4(2c+11) | | 4+7f=f-16 | | z^2=-4 | | x+8=2+7x-5x | | -10x+3x^2-13=0 | | 3(x+2)(3x+1)(x+7)=140 | | 6(-6-2n)=6(12n-6)-9n | | 4(7x+6)=28 | | 3y-2x=8 | | 10x+4y=-8 | | 2x-12x=6 | | u^2-2u+32=(2u-5)(u+2) | | 3x^10=3 | | 5(3x-2)+34x-7=24x-8 | | -7(7-3x)=-4(10-6x) | | 7a^2=19-8a | | x^2+.7x+.1=0 | | 8s(s+4)=s-21 | | 4(7-2b)+2(5b+2)= | | -0.2x-0.3y=0.2 | | -x+5-3x=-55 | | 5x-35=x-13 | | 10x=15x-15 | | 8x-6=5x-12 | | 2(23-x-2y)+2(23-x-7)=20 | | 4(x+3)=3x+3 | | 2(x+2)=3x-4 |